Environmental Discourses and Rhetoric in the Conceptual Space of Architectural Education - Rider, Traci Rose (Enquiry The ARCC Journal for Architectural Research, 2014)
This paper aims to investigate the current state and potential opportunity of strategic environmental discourses and rhetoric in architectural education. Because there is limited research completed on this specific focus, a grounded theory approach was used. In-depth interviews were held with twelve purposefully selected participants, each of whom are prevalently perceived as leaders in incorporating sustainability topics into architectural education. Through a cyclical coding process, larger themes about integrating environmental topics in formal architectural education emerged, with the importance of discourse and rhetoric as one of the primary sub-themes. Different discourses, emphasis on specific terminology, and the implications of each in the conceptual space of architectural educational are explored in the context of both program- and university-level structures. Breaking down the current environmental discourses in these specific contexts offers insight into opportunities to streamline the inclusion of sustainability themes in architectural education. This study concludes with possible avenues for further research regarding environmental discourse and rhetoric in architectural education, and suggestions for application in programs.